Transforming Educational Human Resources to Enhance Institutional Quality and Student Admission Rates - Titi Dewi Jayanti; Roro Rohayati; Khusnul Khotimah; Eni Suprapti; Hengelina; Irnie Victorynie (Journal of Educational Management Research, 2026)
Urban private secondary schools continue to face persistent challenges, particularly related to limited financial resources and declining public trust, which directly affect student enrollment rates. This study aims to analyze how the transformation of educational human resources (HR) contributes to improving school quality and increasing student enrollment. Employing a qualitative research design with a phenomenological approach, data were collected through in-depth interviews with the school principal as the key informant. The data were analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that educational HR transformation, particularly through systematic competency mapping and the implementation of structured coaching and mentoring programs, plays a critical role in enhancing instructional quality and cultivating a professional organizational culture. Furthermore, the integration of a low-cost school policy with continuous HR quality improvement has proven effective in increasing access to education and rebuilding public trust, as evidenced by a notable rise in student enrollment. The study implies that sustainable and strategically managed educational HR transformation serves as a fundamental mechanism for improving school quality and strengthening enrollment performance in urban private secondary schools.